(untitled) (Fiep Bulletin - online, 2015)
The Human being’s health depends 80% on the satisfaction of life itself, which means that the psychic health and the social health of the Modern person has a bigger influence on him /her than their somatic health. In sport, the conquests, the intensive training increase the worry with the athlete’s psychic health. It can be affirmed that the psychic health is an essential component in relation to the general health of the athletes. A disturbance or lack of balance in the psychic health can lead to functional and biological changes, which reflect in the social health and implicate the general health and efficiency the of the team. The target of this research was to determine the athlete’s psychic health level of the Brazilian Olympic women’s handball team. The study group was made up of 15 athletes from the Brazilian Olympic women’s handball team taking part in the 2004 Olympic Games held in Athens. The Kalinine methodology, which bases its analysis on typological peculiarities of the personality, was used to determine the levels of the psychic health of the athletes. To detect the typological peculiarities of the personalities if the athletes, the following tools were used: the “BGYK-I diagnostic software”, the “NCTRFSN Neuro-cronometer”, the EYSENCK questionnaire and the HANYN-SPILBERGER questionnaire. The results of the research show us that the level of psychic health of the athletes was high and very high . Conclusion: From the psychological point of view, the Brazilian Olympic women’s handball team were ready to compete in the Olympic games in Athens.